Peran Budaya Organisasi Dan Kepemimpinan Dalam Meningkatkan Efektivitas Kinerja Dan Pelayanan Pelanggan Arroyan Store - Silvi Aulia Putri (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study aims to analyze the role of organizational culture and leadership in improving the effectiveness of performance and the quality of customer service at Arroyan Store. The method used in this study is a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation studies in the field, and documentation. The research subjects included the business owner and employees of Arroyan Store who were directly involved in business operations. The results of the study indicate that an organizational culture that emphasizes family values, order, and responsibility plays a very important role in shaping employee work behavior that is cooperative and consistent. In addition, the participatory leadership implemented by the business owner of Arroyan Store is also able to create effective work communication and support decision-making that is responsive to operational and customer needs. The synergy between organizational culture and leadership has a positive impact on the effectiveness of employee performance and the quality of service to customers. This study concludes that strengthening organizational culture and leadership is an important strategy in supporting the termination of small-scale service businesses.